Ornithine Transcarbamylase Deficiency in Iranian Children - HR Joshaghani; M Jalali; T Zaman (Tehran University of Medical Sciences, 2003)
Ammonia is a toxic material for mammalians. It is detoxificated and converted to urea in the urea cycle in liver. Each defect in the urea cycle cause increase in blood ammonia level. Ornithine transcarbamylase enzyme (OTC) is the second enzyme in the urea cycle that exists in mitochondria. OTC deficiency is the most common hereditary disorder in the urea cycle. In this study, 45 hyper ammonia patients were selected (2-13 years old) and assayed for serum OTC, serum aspartate aminotransferase (AST), serum alanine aminotransferase (ALT). Four patients (n=45, 8.9%) suffered from OTC deficiency. One patient was male (n=29, 3.4%) and the others were female (n=16, 18.8%). About half of children (53.3) with hyper ammonia have liver disease. Further studies on OTC deficiency and OTC gene mutations in Iran are recommended.